Effect of Dietary Orange Peel Essential Oil and Thermotolerance on Histo-morphometry and Serotonin-immunoreactive Endocrine Cell Numbers in the Small Intestines of Heat Stressed Japanese Quails - Bayrakdar, Ali; Dalkilic, Bestami; Yaman, Mine; Simsek, Ulku Gulcihan; Ciftci, Mehmet (Kafkas Univ, Veteriner Fakultesi Dergisi, 2017)
This study was conducted in order to measure the effects of early period thermal conditioning, feed restriction, supplementation of orange peel essential oil (OEO) into ration or combinations of them on small intestinal morphology and density of serotonin-immunoreactive (IR) endocrine cells (ECs) found in small intestines. 168 7-day-old Japanese quails were divided into six groups of 24-h fasting or thermal conditioning and their subgroups with and without supplementation of OEO (300 ppm) into ration. We determined that fasting and thermal conditioning increased villus height for duodenum in control groups and for jejunum in OEO groups. In addition, we detected that while fasting and thermal conditioning increased villus height/crypt depth (VH/CD) ratio in duodenum and jejunum, these applications did not affect this ratio in ileum. We found that supplementation of OEO into ration increased the number of serotonin-IR ECs in crypts of small intestine. We revealed that early period thermal conditioning increased the number of serotonin-IR ECs in duodenum, jejunum, and ileum especially in groups in which OEO was supplemented into ration. These results indicated that applications of early period thermal conditioning and feed restriction in quails may generally prevent adverse effects, caused by heat stress, on intestinal morphology.
Yeme eklenen portakal kabuğu esansiyel yağının ve termotoleransın sıcaklık stresi uygulanan japon bıldırcınlarında ınce bağırsak histomorfometrisine ve serotonin-immunoreaktif endokrin hücre sayısına etkisi
Keywords: Thermotolerance; Fasting; Orange peel essential oil; Intestinal morphology; Immunohistochemistry; Serotonin